Digital Marketing Alliance on Small Medium Enterprises (SMES): A Systematic Literature Review - Trukan Sri Bahukeling; Arif Imam Suroso; Agus Buono; Popong Nurhayati (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The development of digital marketing continues to grow and increase rapidly. Strengthening digital marketing by SMEs encourages marketing alliances with other parties. Simultaneously, the digital marketing alliance literature accumulated with this growth, but research is still few and not consistently integrated. SMEs are widely regarded as engines of economic growth and a vital contributor to a country's GDP. A brief comprehensive review is needed to help researchers and practitioners understand the adoption of digital marketing alliance systems. This study aims to analyze and classify the literature on digital marketing alliances in SMEs. Design/methodology by conducting literature studies published between 2016-2021 in the journal listed in the Journal Citation Report. It is then analyzed according to a systematic literature review approach involving interpretation-based assessments of research methodologies and critical findings in the study. The direction of this research is expected in the future to have implications for academics and practitioners. The authors' conclusions develop a theoretical model of digital marketing alliance between government and private that is applied to SMEs, impacting to create excellence in the era of digitalization. The originality /value of this research is the first expected to take a holistically integrated approach to study the digital marketing alliance of SMEs. Keywords: digital marketing, marketing alliance, small medium enterprises (smes), literature studies